E1 Signal Processing of the Galileo System in the Navigation Receiver - Lucjan Setlak; Rafał Kowalik (Communications - Scientific letters of the University of Zilina, 2021)
The subject of this article are issues related to the navigation system in the field of analyzing the processed signal in the GNSS system receiver. The main purpose of the work is to discuss the Galileo E1 signal processing methods in the GNSS navigation system receiver, supported by adapted research tools in terms of solving the research problem (analysis, model, simulation tests) and the mathematical apparatus used. Key studies are concentrated around the process of generating the navigation data, dispersing sequences and signal modulation. Thus, when designing a receiver, it is better to use the simulation signals than the real ones, since one can get more control over the properties of the received signal. In the final part of the work, in accordance with the subject of research, based on the developed appropriate research tools, observations and final conclusions were formulated, which have practical applications.